The dark side of leadership : a cross-cultural compendium : with lessons for leaders - Oyewunmi, Adebukola E.; Owens, Gill (Psychologist); Adeola, Ogechi (Productivity Press, 2025)
The corporate landscape is rife with instances of leaders who have left a trail of sinister outcomes.In the last three decades, the research in leadership and organisational sciences has expanded in theoretical and typological breadth to include the dark side. These works have aimed at uncovering the complex interplay of personalities, power dynamics, and organisational cultures that can lead to destructive and unethical behaviours in the workplace. While there are volumes of literature on leadership, there is a dearth of research that integrates dark leadership and cross-cultural norms, perspectives, variances, and interventions. The Dark Side of Leadership: A Cross-Cultural Compendium is a collaborative and transdisciplinary venture that draws on the knowledge and experiences of practitioners and scholars across the globe to explore the contentious and evolving subject of dark leadership. The primary consideration of this book is to explore dark side leadership conceptualisations and manifestations across contexts and provide insights into traits, processes, and outcomes, as well as interventionist paradigms. Hofstede's research demonstrates the fundamental role of national and organisational culture in shaping leadership behaviour. This book comprehensively documents cross-cultural cases, perspectives, and research on the dark side of leadership.
Keywords: Leadership -- Moral and ethical aspects.; Leadership -- Psychological aspects.; Leadership -- Cross-cultural studies.; elektronické knihy; electronic books